A Comment on Barnett and Block on Time Deposit and Bagus and Howden on Loan Maturity Mismatching - Cachanosky, Nicolás (2011)
In Time Deposits, Dimension, and Fraud (2009), William Barnett and Walter Block argue that by borrowing short and lending long there is an over issuance of property rights. Their article, however, does not fully extend the consequences of their contribution. Once this is done, it becomes clearer that their argument suits a great impediment to banking, becoming a possible reason to support rather than to oppose fractional reserve banking. Bagus and Howden (J Bus Ethics 90(3):399–406, 2009) comment on Barnett and Block (J Bus Ethics 88(4):711–716, 2009), the authors claim that while maintaining the illegitimacy of fractional reserve deposits, borrowing short and lending long it is actually not illegitimate. An extension on Bagus and Howden (2009) will show that their line of argumentation can be applied as a defense of fractional reserve banking as well.
Keywords: Maturity mismatching; 100 percent reserve requirement; Fractional reserve banking; Time deposits